Structural, electronic and thermodynamic investigation of Ag2GdSi, Ag2GdSn and Ag2Gd Pb Heusler alloys: First-principles calculations - Zoubir, Mahdjoub Kheireddine (2021)
The strcutral, electronic and thermodynamic proerties of Ag2GdSi, Ag2GdSn and Ag2GdPb Heusler alloys are investigated using first-principles calculations of density functional theory (DFT) through linearized augmented plane waves (FP-LAPW) implemented within Wien2k software package. Structural, electronic and thermodynamic investigations of Ag2GdSi, Ag2GdSn and Ag2GdPb Heusler alloys are performed. Moreover, details regarding the lattice parameters, bulk modulus and its pressure derivative, band structure and density of states are elaborated upon.